POLA KOMUNIKASI ORANGTUA TUNGGAL DALAM MEMBENTUK KEMANDIRIAN ANAK (KASUS DI KOTA YOGYAKARTA) - Yuni Retnowati (Jurnal Ilmu Komunikasi, 2008)
Communication is one of aspect that can be considered in transforming children’s independency. The aims of this research are: (1) examining communication pattern of single parents in transforming children’s independency; (2) analyzing the correlation between surroundings and the characteristic of single parents to communication pattern; (3) analyzing the correlation between surroundings and the characteristic of single parents to children’s independency. This research employed qualitative approach and survey method by collecting data through ques- tionnaire with 25 single parents who are determined by having legal documents issuing by Yogyakarta Religious Court, in-depth interviewed with 10 single parents. Then, data is analyzed descriptively. The results of this research showed that: (1) the interaction and transaction com- munication pattern played a dominant role in transforming children’s independency by internalizing consciousness to be independent and giving children some training; (2) there is no correla- tion between surroundings factor and communication pattern but there is correlation between the characteristic of single parents and communication pattern; (3) there is correlation between surroundings factor and the characteristic of single parents to children’s independency.